1998
DOI: 10.1091/mbc.9.6.1589
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of β-Catenin and Plakoglobin and Shedding of VE-Cadherin during Endothelial Apoptosis: Evidence for a Role for Caspases and Metalloproteinases

Abstract: Growth factor deprivation of endothelial cells induces apoptosis, which is characterized by membrane blebbing, cell rounding, and subsequent loss of cell-matrix and cell-cell contacts. In this study, we show that initiation of endothelial apoptosis correlates with cleavage and disassembly of intracellular and extracellular components of adherens junctions. beta-Catenin and plakoglobin, which form intracellular links between vascular endothelial cadherin (VE-cadherin) and actin-binding alpha-catenin in adherens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
193
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(215 citation statements)
references
References 59 publications
17
193
0
3
Order By: Relevance
“…The mechanism of ectodomain cleavage of adhesion proteins, mediated by MMPs, has been already well described (Lochter et al, 1997;Herren et al, 1998;Noe et al, 2001). MMP-3 and MMP-7 have a role in the shedding of the extracellular domain of E-cadherin, generating a soluble 80 kDa fragment (Noe et al, 2001).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mechanism of ectodomain cleavage of adhesion proteins, mediated by MMPs, has been already well described (Lochter et al, 1997;Herren et al, 1998;Noe et al, 2001). MMP-3 and MMP-7 have a role in the shedding of the extracellular domain of E-cadherin, generating a soluble 80 kDa fragment (Noe et al, 2001).…”
Section: Discussionmentioning
confidence: 90%
“…Given that MMPs were already described to shed the extracellular domains of membrane glycoproteins, including E-cadherin, giving rise to a soluble fragment with pro-invasive activity (Lochter et al, 1997;Herren et al, 1998;Noe et al, 2001), we looked forward for the presence of soluble fragments of cadherins in the conditioned medium from the studied cell lines. Surprisingly, no significant differences were observed concerning the presence of soluble E-cadherin (sE-cad); however, sP-cad was increased 8.7-fold in the conditioned medium from MCF-7/AZ.Pcad cells (Figure 6c).…”
Section: Soluble P-cadherin Induces Breast Cancer Cell Invasionmentioning
confidence: 99%
“…Herein, catenins are the molecular linker between the microfilaments and specialized transmembrane proteins, so-called cadherins, that make contact to cadherins on the opposing cell surface. Herren et al (1998) furthermore found cleavage of the extracellular domains of VE-cadherin in apoptotic endothelial cells by secreted matrix metallo-proteinases (MMP). Thus, the rapid decrease of impedance after induction of apoptosis may be the result of both processes: disintegration of adherens junctions in concert with proteolysis of actin filaments.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the absence of E-cadherin can lead to an accumulation of free bcatenin and increased transactivation, which can be competed out by transient transfections with E-cadherin (Orsulic et al, 1999). Beta-catenin was recently found to be involved in apoptosis (Herren et al, 1998). Their finding that caspases have the capacity to cleave b-catenin proteolytically at the N-and C-terminal, which will reduce a-catenin binding, release actin filaments and reduce cell -cell interaction, indicates that b-catenin has an important role at a late stage of apoptosis.…”
Section: Discussionmentioning
confidence: 99%